Efektivitas Penambahan Ekstrak Temulawak dan Daun Sirih serta Lama Penyimpanan terhadap Kualitas Minuman Herbal - Sihombing, Dewi Restuana (Universitas Katolik Santo Thomas Medan, 2020)
This study aims to determine the effect of the comparison of the concentration of temulawak extract And sirih leaves on the manufacture of herbal drink. This research was conducted in the laboratory of processing and Management of Agricultural Products, Faculty of Agriculture, Santo Thomas Catholic University, North Sumatra, Medan. This research was conducted with a factorial Complete Randomized Design (CRD), which consisted of two treatment factors. The first factor Comparison of the concentration of Temulawak and Betel Leaf with a code (K), consists of 5 levels, namely: K0 = Temulawak: sirih leaves = 100%: 0%, K1 = Temulawak: sirih leaves = 80%: 20%, K2 = Temulawak: sirih leaves = 70%: 30%, K3 = Temulawak: sirih leaves = 60%: 40%, K4 = Temulawak: sirih leaves = 50%: 50%. The second factor is the comparison of storage duration with a code (L), consisting of 4 levels, namely: L1 = 1 Week, L2 = 2 Weeks, L3 = 3 Weeks, L4 = 4 Weeks.